2011
DOI: 10.2147/ijn.s17503
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intravenous amphotericin B-polybutylcyanoacrylate nanoparticles against cryptococcal meningitis in mice

Abstract: Amphotericin B deoxycholate (AmB), a classic antifungal drug, remains the initial treatment of choice for deep fungal infections, but it is not appropriate for treatment of cryptococcal meningitis due to its inability to pass through the blood–brain barrier (BBB). We examined the efficacy of amphotericin B-polybutylcyanoacrylate nanoparticles (AmB-PBCA-NPs) modified with polysorbate 80 that had a mean particle diameter less than 100 nanometers (69.0 ± 28.6 nm). AmB-PBCA-NPs were detected in the brain 30 minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 21 publications
(20 reference statements)
0
38
0
Order By: Relevance
“…As an example for drug delivery using polymeric nanoparticles a few studies can be mentioned. An efficient brain delivery was demonstrated using amphotericin B loaded and polysorbate 80 (Tween Ò 80) containing poly(butyl cyanoacrylate) nanoparticles (PBCA-NP) (Xu et al, 2011). It has been suggested that Tween Ò 80 coated PBCA-NP were processed by endothelial brain cells via endocytosis after an analgesic activity of dalargin was demonstrated in mice following the administration of dalargin loaded PBCA-NP (Kreuter et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…As an example for drug delivery using polymeric nanoparticles a few studies can be mentioned. An efficient brain delivery was demonstrated using amphotericin B loaded and polysorbate 80 (Tween Ò 80) containing poly(butyl cyanoacrylate) nanoparticles (PBCA-NP) (Xu et al, 2011). It has been suggested that Tween Ò 80 coated PBCA-NP were processed by endothelial brain cells via endocytosis after an analgesic activity of dalargin was demonstrated in mice following the administration of dalargin loaded PBCA-NP (Kreuter et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Another type of nanoparticle, poly butyl cyanoacrylate nanoparticles (AMB-PBCA-NP) coated with polysorbate 80 were detected in the brain 30 min after systemic administration and had a higher brain tissue concentration than LAMB. In addition, the survival rate of mice treated with AMB-PBCA-NP (80%) was significantly higher than LAMB (60%) and deoxycholate AMB (0%) [110]. Shao et al (2010) demonstrated that an angiopep-2 modified PE-PEG (1,2-Distearoyl-sn -glycero-3-phosphoethanolamine-N-[methoxy (polyethylene glycol)-2000]) based micellar drug delivery system loaded with AMB (Angiopep-PEG-PE/AMB) was more effectively transported across the BBB than the deoxycholate AMB and the micelle without angiopep-2 in in vitro and in vivo assays.…”
Section: Drug Delivery Systemsmentioning
confidence: 92%
“…An in vitro study comparing the microemulsion AmB to deoxycholate AmB formulations in human blood cells demonstrated that the encapsulation significantly reduces hemolysis. The conventional AmB presented 100% hemolysis at the concentration of 5 μl/ml while the other formulation presented approximately 10% (Nahar et al, 2008); the nanoparticles presented less than 1% hemolysis at the concentration of 200 uL/mL (Xu et al, 2011). …”
Section: Hematotoxicitymentioning
confidence: 95%